Peningkatan Hasil Belajar Melalui Model Inquiry Termbimbing Pada Siswa Kelas VA di SDN 002 Samarinda Utara - Wika Fradila; Gamar Al Haddar Gamar (Journal of diversity in learning (JDIL), 2022)
This study aims to improve student learning outcomes by using a guided inquiry model approach to learning science. In the VA class of SDN 002 North Samarinda, this study used classroom action research (CAR). This research was motivated by the low learning outcomes of class VA students at SDN 002 North Samarinda because teachers used more of the lecture approach and made learning activities in class less interesting. Cycle III consisting of three meetings per cycle was used for this research. The research subjects were 25 VA students at SDN 002 North Samarinda consisting of 14 boys and 11 girls. When conducting research, the guided inquiry approach can improve student learning outcomes. The percentage of student learning outcomes increased from 69.6% in the first cycle in the poor category to 76.8% in the second cycle in the good category to 80.52 percent in the third cycle in the very good category. The following difficulties were found by researchers in using the guided inquiry model: students who were still passive in class and less effective in practicing the teacher's teaching tactics. The conclusions of this study support the notion that the use of guided inquiry learning models is very beneficial for student learning outcomes. Therefore, the guided inquiry approach can be used as a teaching strategy for teaching science topics in elementary schools.